Vascularised composite allotransplants: Transplant of upper extremities and face - Subramania Iyer (Indian Journal of Plastic Surgery)
Transplantation of solid organs and bone marrow has become a highly acceptable and often the only available clinical solution in many situations. It has been practiced across the globe for quite a long time since the first kidney transplant in 1954. Transplantation of tissues other than these, which was termed composite tissue allotransplantation and currently as vascularised composite allotransplantation (VCA) is gaining acceptance as a solution for complex reconstructive problems. This involves the transfer of multiple types of tissue such as bone, muscle, nerve, skin and blood vessels. The advantage of these over the conventional reconstructive methods is its ability to give aesthetically and functionally superior equal composite substitute to the missing or deformed part. The composite tissues transplanted commonly include the upper extremities, face and abdominal wall. Among these, hand transplants were the first to be done and have been carried out more than any other VCA. This article reviews the current scenario of VCA especially of the hand and face, in the light of experience of the two bilateral hand transplants done recently in India.